2022
DOI: 10.3389/fpls.2022.891155
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Microbiome in the Phyllo-Endosphere of Highly Specialized Rock Spleenwort

Abstract: Bacteria communities associated with plants have been given increasing consideration because they are arguably beneficial to their host plants. To understand the ecological and evolutionary impact of these mutualistic associations, it is important to explore the vast unknown territory of bacterial genomic diversity and their functional contributions associated with the major branches of the tree-of-life. Arguably, this aim can be achieved by profiling bacterial communities by applying high throughput sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 102 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…Endophytic bacteria can significantly change the production and concentration of secondary metabolites in various areas of medicinal plants or promote their production and based on that find different biological applications. Endophytes have been studied for a variety of purposes from investigating their interaction with host plants and effects on plant and soil health (Raimi, Adeleke, 2021;Masocha et al, 2022).…”
Section: Issn 1392-3196mentioning
confidence: 99%
“…Endophytic bacteria can significantly change the production and concentration of secondary metabolites in various areas of medicinal plants or promote their production and based on that find different biological applications. Endophytes have been studied for a variety of purposes from investigating their interaction with host plants and effects on plant and soil health (Raimi, Adeleke, 2021;Masocha et al, 2022).…”
Section: Issn 1392-3196mentioning
confidence: 99%
“…Chigurupati et al (2021) recorded the incredible capacity of endophytic microbes to produce bioactive compounds as an antioxidant and antidiabetic agents from Durio zibethinus. Moreover, the endophytic bacteria studies on pteridophyte (ferns and its allies) species has been reported on many taxa, e.g., Dryopteris (Das et al 2017), Ophioglossum (Mukherjee et al 2017), Azolla (Yang et al 2022), and Asplenium (Masocha et al 2022).…”
Section: Introductionmentioning
confidence: 99%